2015
DOI: 10.1589/jpts.27.2405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ankle balance taping with kinesiology tape for a patient with chronic ankle instability

Abstract: [Purpose] To report the effects of ankle balance taping for a patient with chronic ankle instability (CAI). [Subject] A 33-year-old man with a 10 year history of chronic ankle stability. [Methods] ABT with kinesiology tape was performed for 2 months (average, 16 h/day) around the right ankle. [Results] At the end of two months, no ankle instability was noted when ascending and descending the stairs, jumping, turning, operating the pedals while driving, and lifting heavy objects. [Conclusion] The repeated use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 11 publications
(13 reference statements)
0
24
0
2
Order By: Relevance
“…Proprioceptive signals are sent by afferent fibers from proprioceptive receptors which are located in the ligaments, capsules, transdermal tissues and muscles, and muscle afferent fibers provide the most important information to most of the joints in the body. When there is a decline in proprioceptive control, it is highly likely to present with declines in postural control and protective reflex, joint movement, and the ability to control perturbation 9 , 10 ) . Proprioceptive control plays an important role in reducing functional instability and re-injury of the joints, hence a decline in proprioceptive control may lead to a reduction in joint stability and an increase in the injury frequency rate 10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Proprioceptive signals are sent by afferent fibers from proprioceptive receptors which are located in the ligaments, capsules, transdermal tissues and muscles, and muscle afferent fibers provide the most important information to most of the joints in the body. When there is a decline in proprioceptive control, it is highly likely to present with declines in postural control and protective reflex, joint movement, and the ability to control perturbation 9 , 10 ) . Proprioceptive control plays an important role in reducing functional instability and re-injury of the joints, hence a decline in proprioceptive control may lead to a reduction in joint stability and an increase in the injury frequency rate 10 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sprained ankle was protected from reinjury through the mechanical effects of AET application. Previous studies have reported that kinesiology tape application to an ankle with instability 10 ) and eversion sprain 11 ) reduced pain and improved stability. Therefore, healing of ankle inversion sprain was possible.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effect of KT on patellofemoral pain syndrome, ankle instability, whiplash injury, spasticity, and low back pain 9 , 10 , 11 , 12 , 13 ) . There have been only two studies of the effectiveness of KT on mechanical neck pain 7 , 14 ) , and to date, one study and a single case report have evaluated the effects of KT use in patients with myofascial pain 15 , 16 ) .…”
Section: Introductionmentioning
confidence: 99%